2020
DOI: 10.1111/nph.16483
|View full text |Cite
|
Sign up to set email alerts
|

CEP receptor signalling controls root system architecture in Arabidopsis and Medicago

Abstract: Root system architecture (RSA) influences the effectiveness of resources acquisition from soils but the genetic networks that control RSA remain largely unclear.We used rhizoboxes, X-ray computed tomography, grafting, auxin transport measurements and hormone quantification to demonstrate that Arabidopsis and Medicago CEP (C-TERMINALLY ENCODED PEPTIDE)-CEP RECEPTOR signalling controls RSA, the gravitropic set-point angle (GSA) of lateral roots (LRs), auxin levels and auxin transport.We showed that soil-grown Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…Our data highlights the importance of CEPR1 activity in the reproductive bolt for the delivery of nutrients for yield formation. The apparent perturbation of nitrogen status in cepr1 bolts suggests that CEPR1 plays a broader role in controlling nitrogen homeostasis at the whole-plant level, beyond roles previously identified in root nitrogen acquisition, root system architecture and nodulation (Huault et al, 2014;Tabata et al, 2014;Mohd-Radzman et al, 2016;Ohkubo et al, 2017;Chapman et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our data highlights the importance of CEPR1 activity in the reproductive bolt for the delivery of nutrients for yield formation. The apparent perturbation of nitrogen status in cepr1 bolts suggests that CEPR1 plays a broader role in controlling nitrogen homeostasis at the whole-plant level, beyond roles previously identified in root nitrogen acquisition, root system architecture and nodulation (Huault et al, 2014;Tabata et al, 2014;Mohd-Radzman et al, 2016;Ohkubo et al, 2017;Chapman et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The interaction of the root-derived CEPs with CEPR1 in the shoot vasculature triggers the upregulation of phloem-mobile shootto-root signals, namely the glutaredoxins CEP DOWNSTREAM 1 (CEPD1) and CEPD2, that upregulate the level of nitrate transporter expression in roots selectively exposed to high nitrate (Ohkubo et al, 2017). Recently, we demonstrated that local and systemic CEP-CEPR1 signalling curtails the expenditure of resources to control lateral root growth in response to elevated shoot-derived carbon (Chapman et al, 2019), and that systemic CEP-CEPR1 signalling controls aspects of root system architecture in soil (Chapman et al, 2020). CEP-CEPR1 signalling also controls main root growth in Arabidopsis (Delay et al, 2013b;Delay et al, 2019).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The increased acropetal polar auxin transport might, however, be related to the MtYUC2 upregulation observed in cra2. Recently, acropetal polar auxin transport and shoot auxin levels were shown to modulate RSA systemically from shoots depending on MtCRA2 by regulating the angle of lateral root emergence relative to the gravity vector (Chapman et al, 2020).…”
Section: Mtcra2 In Roots (mentioning
confidence: 99%
“…In addition, CEP family peptides impact the expression of nitrate transporters in the root, signal via XYLEM INTERMIXED WITH PHLOEM 1 (XIP1)/CEP RECEPTOR 1 (CEPR1) and CEPR2 and induce phloem-specific polypeptides in leaves that act as long-distance mobile signals trans-located to the root [7,8]. Recently, it was suggested that CEP-CEPRdependent signalling controls Arabidopsis and Medicago root system architecture, gravitropic set-point angle of lateral roots, shoot auxin levels and rootward auxin transport [9]. However, based on the diverse expression patterns of CEP family peptides [10] and a recently described role in sucrose-dependent enhancement of lateral root growth [11], these peptides likely play important roles beyond nitrogen acquisition.…”
Section: Downloaded Frommentioning
confidence: 99%